2023
DOI: 10.1101/2023.10.11.561922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linkingin vivomuscle dynamics toin situforce-length and force-velocity reveals that guinea fowl lateral gastrocnemius operates at shorter than optimal lengths

MJ Schwaner,
DL Mayfield,
E Azizi
et al.

Abstract: Force-length (F-L) and force-velocity (F-V) properties characterize skeletal muscles intrinsic properties under controlled conditions, and it is thought that these properties can inform and predict in vivo muscle function. Here, we map dynamic in vivo operating range and mechanical function during walking and running, to the measured in situ F-L and F-V characteristics of guinea fowl (Numida meleagris) lateral gastrocnemius (LG), a primary ankle extensor. We use in vivo patterns of muscle tendon force, fascicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 92 publications
0
2
1
Order By: Relevance
“…Second, we found that the change of the force-length relationship with activation was not correct, while for the force-velocity relationship, it was correct. For our network, the optimal fibre length increased with increasing activation, while previous experiments have shown that it decreases with increasing activation (e.g., [12,32]). However, the maximum shortening velocity decreased with decreasing activation, as was previously shown [13].…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Second, we found that the change of the force-length relationship with activation was not correct, while for the force-velocity relationship, it was correct. For our network, the optimal fibre length increased with increasing activation, while previous experiments have shown that it decreases with increasing activation (e.g., [12,32]). However, the maximum shortening velocity decreased with decreasing activation, as was previously shown [13].…”
Section: Discussioncontrasting
confidence: 48%
“…Therefore, this inaccuracy could be explained by a lack of training data in these regions, since most data was recorded at low and medium activation, and fibre lengths and velocities closer to optimal and isometric conditions. Another reason could be found in a recent study by Schwaner et al [32], who found that in-vivo force-length dynamics might not be represented well by in-situ measurements of the force-length relationship. Therefore, we need to find additional approaches to further validate the neural networks for application across species.…”
Section: Discussionmentioning
confidence: 98%
“…These plots highlight the variation in observed strain patterns during different modes of locomotion. Data for (a) and (b) are recreated from [23,24], respectively.…”
Section: Resultsmentioning
confidence: 99%